Aplikasi Game Sejarah Perang Dunia II di Sausapor Papua Barat: World War II History Game Application In Sausapor West Papua - Vincent Manemi; Arthur M. Rumagit; Yuri V. Akay (Jurnal Teknik Informatika, 2024)
History is a series of significant events or occurrences in the past that have influenced the development of a civilization, nation, state, or the world. There are many historical stories that have been adapted into works of art such as paintings, monuments, films, games, and more. It is through these adaptations that history serves as a medium of learning for individuals who seek to understand the world's past. Therefore, an engaging learning approach is needed, especially for the younger generation. By designing a game that integrates historical events, particularly the struggle for independence, we can enhance the interest of the youth in learning history through an exciting and enjoyable method. The objective of this research is to develop a First Person Shooter (FPS) warfare game set in Sausapor in the year 1944, which will be used as an educational tool to increase public interest in learning history. The game development process will utilize Unreal Engine as the game engine, combined with the Game Development Life Cycle (GDLC) methodology. Based on the research objectives and outcomes, it is anticipated that this game will enhance the enthusiasm for learning history and improve understanding of the events surrounding World War II in Sausapor in 1944.